Towards a New Design that Breaks the Traditional Structural Base for Building Design - Dorra, Mohame Medhat; Saleh, Mona Mohamed (الجمعية العربية للحضارة والفنون الإسلامية, 2024)
في وقتنا الحالي وعصرنا الرقمي ومجتمع المعلومات اختلف التفكير في الشكل المعماري بشكل كبير فقد ظهرت مفاهيم وتقنيات وعمليات تصميم جديده تكسر القاعدة الهيكلية للعمارة وتوجه الفكر نحو الحرية في الشكل والتصميم ودراسة العلاقة بينهم. كما أن نظرية الهيكل العظمى أفسحت المجال لنظرية الجلدية والتدفق والأسطح المستمرة. وهي كلها عبارة عن تحول معماري يوثق تطور العلاقة الجديدة بين المهندس المعماري والتكنولوجيا الحديثة وعلى ذلك فقد أكتسب السطح عمقا وتعقيدا وسلوكيات جديده قابلة للتغير وهنا تكمن المشكلة البحثية. ويسعي البحث إلى إثبات أن المبني غير قائم على فكرة الكمرات والأعمدة والواجهات التقليدية كالعظام التي يكسوها الجلد بل أصبح المبني قائم على فكرة أنه مكون من العضلات والأعصاب. كما يسعي البحث إلى الاستفادة من التوجه الجديد نحو عمارة حرة تكسر الواقع الافتراضي بشكل كبير ودراسة التطور لمفهوم الشكل في العمارة والمورفولوجيا للمبنى وتطورها وتحليل بعض المشاريع الداعمة لهذا الفكر الحديث. Thinking about architectural form differed significantly, as new concepts, techniques and design operations have emerged that broke the base of architecture and directed thought towards freedom in form, design and studying the relationship between them. Also, the theory of the skeleton gave way to its leather theory, flow and continuous surfaces, which are all of an architectural shift that documents the development of the new relationship between the engineer and technology, and on that the surface has gained depth, complications and new behaviors have changed, and here lies the research problem as the research seeks to prove that the building is not existing on the idea of the traditional beams, columns and facades, such as the bones that the skin covers. Rather, the building has become based on the idea that it is made up of muscles and nerves. The research also seeks to take advantage of the new trend towards a free building that greatly breaks the virtual reality and studying the development of the concept of form in architecture and morphology of the building and its development and analyzing some of the projects that support this modern thought.
Keywords: التصميم المعماري -- التكنولوجيا الرقمية -- الفكر المعماري -- العمارة التفكيكية